PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING LEARNING (CTL) DENGAN STRATEGI INKUIRI TERHADAP HASIL BELAJAR SISTEM GERAK MANUSIA - Nursafiah, Nursafiah; Kurniawati, Kurniawati; Fajriana, Nurul; Rosma, Fatemah (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study aimst determine the effect of the CTL learning model with inquiry strategies on student learning outcomes at SMPN 4 Kutacane. This research uses experimental methods. The population in this study was class VIII students, totaling 85 students. The sample consisted of 44 students consisting of two classes, namely class VIII-2 with 22 students as the experimental class and class VIII/3 as the control class. Data codellection was carried out through pretest and posttest. Data on improving learning outcomes is in the form of normalized gain (N-Gain). The difference in the average N_Gain of the experimental class and the control class was analyzed using an independent sample t-test. The average value of the experimental class is higher than the control class. The results of the t test show that the t value = 2.68 and the t table value = 2.02 (t count > t table) at a significance level of 0.05 which shows that Ho is rejected and Ha is accepted. That there is an influence of the CTL learning model with inquiry strategies on student learning outcomes in human movement systems material.